Developing Children's Creativity Through the TikTok Social Media Platform - Budiarti, Erna; Kurniati , Kartika Nurwita (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
Stimulating children's creativity through social media is important by utilizing platforms that are relevant to their interests and daily interactions. This research aims to determine the benefits of using smartphone technology in stimulating creativity in early childhood through exploratory whipping activities. With the increasing adoption of technology into various aspects of life, including early childhood education, it is important to understand its positive and negative impacts. This research method uses a qualitative approach with a case study approach and focused observation on group B children at RA Al-Islam Petabumi, Seberida District, Indragiri Hulu Regency, Riau Province who are involved in TikTok exploration activities using smartphones. Data collection was carried out through direct observation, interviews, and field notes. This research shows that the use of smartphone technology, especially through applications such as TikTok, can trigger creativity in young children. By taking part in various creative content and challenges on TikTok, children can engage in a process of self-exploration that allows them to develop their creative skills. This shows that social media can be an effective tool for stimulating imagination and innovation in young children. Keywords: early childhood education, creativity, social media TikTok References: Adawiyah, D. P. R. (2020). Pengaruh Penggunaan Aplikasi TikTok Terhadap Kepercayaan Diri Remaja Di Kabupaten Sampang. In Jurnal Komunikasi. https://doi.org/10.21107/ilkom.v14i2.7504 Aditya, B. R., Andrisyah, Ismiatun, A. N., Atika, A. R., & Permadi, A. (2021). Digital disruption in early childhood education: A qualitative research from teachers’ perspective. Procedia Computer Science, 197(2021), 521–528. https://doi.org/10.1016/j.procs.2021.12.169 Aisyah, S., Novita, D., Prastati, T., Chandrawati, T., & Dewi, A. C. (2023). Digital Literacy Learning Module Improves Knowledge of Healthy Food in Indonesian PAUD Students. 11, 31–42. Aktaş, İ. (2022). Research Trends on the Use of Technology in Early Childhood Science Education: Bibliometric Mapping and Content Analysis. In Shanlax International Journal of Education. https://doi.org/10.34293/education.v10is1-aug.4454 Alelaiwi, A., Alghamdi, A., Shorfuzzaman, M., Rawashdeh, M., Hossain, M. S., & Muhammad, G. (2015). Enhanced engineering education using smart class environment. Computers in Human Behavior, 51, 852–856. https://doi.org/https://doi.org/10.1016/j.chb.2014.11.061 Alfoudari, A. M., Durugbo, C. M., & Aldhmour, F. M. (2021). Understanding socio-technological challenges of smart classrooms using a systematic review. Computers & Education, 173, 104282. https://doi.org/https://doi.org/10.1016/j.compedu.2021.104282 Amini, M. (2022). Family Literacy Program for Improving the Ability to Know Letters in Early Childhood. In International Journal of Emerging Issues in Early Childhood Education. https://doi.org/10.31098/ijeiece.v4i2.895 Anisa, M., Putri, R. N., Regina, Y., & Nugraha, D. (2022). Pengembangan Media Tiktok Pada Mata Pelajaran IPS Perubahan Sosial Budaya Sebagai Modernisasi Bangsa Di Sekolah Dasar. In Jurnal Basicedu. https://doi.org/10.31004/basicedu.v6i4.2982 Anisyah, N., Indrawati, Hafizotun, L., Marwah, S., Yumarni, V., & Dn, N. A. (2021). Orang Tua Kreatif Untuk Anak Usia Dini Di Masa Pandemi Covid-19 Melalui Kegiatan Parenting. In Murhum Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.37985/murhum.v2i1.26 Ansari, J. A. N., & Khan, N. M. (2020). Exploring the Role of Social Media in Collaborative Learning the New Domain of Learning. In Smart Learning Environments. https://doi.org/10.1186/s40561-020-00118-7 Antara, I. G. W. S., & Dewantara, K. A. K. (2022). E-Scrapbook: The Needs of HOTS Oriented Digital Learning Media in Elementary Schools. In Journal for Lesson and Learning Studies. https://doi.org/10.23887/jlls.v5i1.48533 Ariani, N. W. T., Gde, D. W. I., & Ketut, W. A. A. (2022). Penerapan Pembelajaran Berbasis Otak Di Paud Dengan Permainan Puzzle. In Pratama Widya Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.25078/pw.v7i1.238 Astuti, R., & Aziz, T. (2019). Integrasi Pengembangan Kreativitas Anak Usia Dini Di TK Kanisius Sorowajan Yogyakarta. In Jurnal Obsesi Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.31004/obsesi.v3i2.99 Azizah, A. R., Samawi, A., & Anisa, N. (2021). Dampak Implementasi Pembelajaran Daring Terhadap Karakter Anak Di Masa Pandemi Covid-19. In Al-Hikmah Indonesian Journal of Early Childhood Islamic Education. https://doi.org/10.35896/ijecie.v5i2.202 Blevins, B., LeCompte, K., & Wells, S. (2014). Citizenship education goes digital. The Journal of Social Studies Research, 38(1), 33–44. https://doi.org/https://doi.org/10.1016/j.jssr.2013.12.003 Budiarti, E., & Yasmin Adar, S. (2023). Impact of Digital Media on Social-Emotional Development in Early Childhood: A Case Study at TK Kartika XX-46 Kendari. Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 8(2), 89–98. https://doi.org/10.14421/jga.2023.82-04 Dewi, N. P. S., & Sugito, S. (2022). Digital Fairy Tales: Children’s Literacy Development During the Covid-19 Pandemic. In Indonesian Journal of Educational Research and Review. https://doi.org/10.23887/ijerr.v5i2.49066 Drupadi, R., Nawangsasi, D., Fatmawati, N., & Sugiana, S. (2022). Pengaruh Digital Literasi Terhadap Perilaku Sosial Anak Usia Dini. In Jce (Journal of Childhood Education). https://doi.org/10.30736/jce.v6i2.1084 Fajriati, R., Na’imah, N., Hibana, H., Putro, K. Z., & Labziah, L. (2022). Pola Komunikasi dalam Proses Pembelajaran di Masa Pandemi Covid-19. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(5), 3877–3888. https://doi.org/10.31004/obsesi.v6i5.1730 Fakhriyani, D. V. (2016). Pengembangan Kreativitas Anak Usia Dini. Wacana Didaktika, 4(2), 193–200. https://doi.org/10.31102/wacanadidaktika.4.2.193-200 Given, L. M., Winkler, D., Willson, R., Davidson, C., Danby, S., & Thorpe, K. (2016). Watching Young Children “Play” With Information Technology: Everyday Life Information Seeking in the Home. In Library & Information Science Research. https://doi.org/10.1016/j.lisr.2016.11.007 Guntarto, B., & Sevrina, N. (2018). The Role of Parents in the Use of Media for Early Childhood in Suburban Jakarta. https://doi.org/10.2991/secret-18.2018.12 Hardiyanti, W. D. (2020). Aplikasi Bermain Berdasarkan Kegiatan Seni Lukis Untuk Stimulasi Kreativitas Anak Usia 5-6 Tahun. In Jurnal Pendidikan Anak. https://doi.org/10.21831/jpa.v9i2.31664 Hill, D. L., Ameenuddin, N., Chassiakos, Y. R., Cross, C., Hutchinson, J., Levine, A., Boyd, R., Mendelson, R. A., Moreno, M., & Swanson, W. S. (2016). Media and Young Minds. In Pediatrics. https://doi.org/10.1542/peds.2016-2591 Hunt, E. A. (2023). Media literacy and digital citizenship (B. B. T.-E. of C. and A. H. (First E. Halpern-Felsher (ed.); pp. 372–384). Academic Press. https://doi.org/https://doi.org/10.1016/B978-0-12-818872-9.00144-8 Husnaini, D., & Yaswinda, Y. (2022). Pengaruh Kreasi Kulit Jagung Terhadap Pengembangan Kreativitas Anak Usia 5-6 Tahun. In Jurnal Obsesi Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.31004/obsesi.v6i6.2956 Israwati, I., Lukman, L., & Hamid, A. N. (2022). Efektivitas Media Flashcard Untuk Meningkatkan Kemampuan Kognitif Anak Usia Dini. In Sultra Educational Journal. https://doi.org/10.54297/seduj.v2i1.214 Kafai, Y. B., & Burke, Q. (2015). Constructionist Gaming: Understanding the Benefits of Making Games for Learning. In Educational Psychologist. https://doi.org/10.1080/00461520.2015.1124022 Kisno, Wibawa, B., & Khaerudin. (2022). Digital Storytelling for Early Childhood Creativity: Diffusion of Innovation “3-D Coloring Quiver Application Based on Augmented Reality Technology in Children’s Creativity Development.” In International Journal of Online and Biomedical Engineering (Ijoe). https://doi.org/10.3991/ijoe.v18i10.32845 Kurniasih, S. (2022). Pembelajaran Inovatif Dengan Media Video Untuk Meningkatkan Kemampuan Membaca Permulaan Pada Usia 5-6 Tahun. In Jp2kg Aud (Jurnal Pendidikan Pengasuhan Kesehatan Dan Gizi Anak Usia Dini). https://doi.org/10.26740/jp2kgaud.2022.3.1.87-96 Laidlaw, L., O’Mara, J., & Wong, S. S. H. (2019). ‘This is your brain on devices’: Media accounts of young children’s use of digital technologies and implications for parents and teachers. Contemporary Issues in Early Childhood, 22(3), 268–281. https://doi.org/10.1177/1463949119867400 Latifah, A. (2020). Peran Lingkungan Dan Pola Asuh Orang Tua Terhadap Pembentukan Karakter Anak Usia Dini. In (Japra) Jurnal Pendidikan Raudhatul Athfal (Japra). https://doi.org/10.15575/japra.v3i2.8785 Lestari, N. S., Zulkarnain, Z., & Prisuna, B. F. (2022). Meningkatkan Kreativitas Anak Usia Dini Melalui Strategi Menggambar Dari Angka Di Tk Tunas Bangsa. In Jea (Jurnal Edukasi Aud). https://doi.org/10.18592/jea.v8i1.6242 Literat, I., & Kligler-Vilenchik, N. (2023). TikTok as a Key Platform for Youth Political Expression: Reflecting on the Opportunities and Stakes Involved. In Social Media + Society. https://doi.org/10.1177/20563051231157595 Livingstone, S., Ólafsson, K., & Haddon, L. (2014). Children’s Use of Online Technologies in Europe: A review of the European evidence base. LSE, London: EU Kids Online Revised Edition., 2014(September), 40. Luna-Nevarez, C., & McGovern, E. (2018). On the Use of Mobile Apps in Education: The Impact of Digital Magazines on Student Learning. Journal of Educational Technology Systems, 47(1), 17–31. https://doi.org/10.1177/0047239518778514 Luo, W., Berson, I. R., Berson, M. J., & Li, H. (2021). Are early childhood teachers ready for digital transformation of instruction in Mainland China? A systematic literature review. Children and Youth Services Review, 120, 105718. https://doi.org/https://doi.org/10.1016/j.childyouth.2020.105718 Magdalena, I., Fatakhatus Shodikoh, A., Pebrianti, A. R., Jannah, A. W., Susilawati, I., & Tangerang, U. M. (2021). Pentingnya Media Pembelajaran Untuk Meningkatkan Minat Belajar Siswa Sdn Meruya Selatan 06 Pagi. EDISI : Jurnal Edukasi Dan Sains, 3(2), 312–325. Maharani, D., & Budiarti, E. (2022). Pengaruh Media Digital & Mutu Perangkat Terhadap Kemampuan Bahasa Pada AUD Melalui Konten Youtube. Jurnal Jendela Pendidikan, 2(03), 429–434. https://doi.org/10.57008/jjp.v2i03.240 Mardliyah, S., Yulianingsih, W., & Putri, L. S. R. (2020). Sekolah Keluarga: Menciptakan Lingkungan Sosial Untuk Membangun Empati Dan Kreativitas Anak Usia Dini. In Jurnal Obsesi Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.31004/obsesi.v5i1.665 Marsh, J., Plowman, L., Yamada-Rice, D., Bishop, J. C., Lahmar, J., Scott, F., Davenport, A., Davis, S., French, K., Piras, M., Thornhill, S., Robinson, P., & Winter, P. (2015). Exploring Play and Creativity in Pre- Schoolers ’ Use of Apps: A Report for Early Years Practitioners. Technology and Play, 203. Marwiyati, S., & Istiningsih, I. (2020). Pembelajaran Saintifik Pada Anak Usia Dini Dalam Pengembangan Kreativitas Di Taman Kanak-Kanak. In Jurnal Obsesi Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.31004/obsesi.v5i1.508 Mayar, F., Uzlah, U., Nurhamidah, N., Rahmawati, R., & Desmila, D. (2022). Pengaruh Lingkungan Sekitar Untuk Pengembangan Kreativitas Anak Usia Dini. In Jurnal Obsesi Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.31004/obsesi.v6i5.2665 Montag, C., Yang, H., & Elhai, J. D. (2021). On the Psychology of TikTok Use: A First Glimpse From Empirical Findings. In Frontiers in Public Health. https://doi.org/10.3389/fpubh.2021.641673 Munasti, K., Purnama, S., Winarti, W., Mutmainnah, M., Nessa, R., Fitriani, D., Aziz, U. B. A., Saptiani, S., Rosmiati, R., & Rahmi, R. (2022). Aplikasi TikTok Sebagai Alternatif Perkembangan Anak Usia Dini. In Jurnal Obsesi Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.31004/obsesi.v6i6.2981 Muslikhah, H., & Pamungkas, J. (2022). Penggunaan Ruang Media Audio Visual Pada Kegiatan Pengembangan Seni Sebagai Ajang Kreatifitas Anak. In Jurnal Obsesi Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.31004/obsesi.v6i6.2853 Neumann, M. M. (2020). The Impact of Tablets and Apps on Language Development. Childhood Education, 96(6), 70–74. https://doi.org/10.1080/00094056.2020.1846394 Ott, M., & Pozzi, F. (2012). Digital Games as Creativity Enablers for Children. In Behaviour and Information Technology. https://doi.org/10.1080/0144929x.2010.526148 Prasanti, D., & Aisha, S. (2023). Peningkatan Kreativitas Anak Usia Dini Melalui Permainan Sebagai Edukasi Media Belajar Kreatif Di PAUD Kabupaten Karawang. In Jurnal Gema Ngabdi. https://doi.org/10.29303/jgn.v5i1.319 Rahardaya, A., & Irwansyah, I. (2021). Studi Literatur Penggunaan Media Sosial Tiktok Sebagai Sarana Literasi Digital Pada Masa Pandemi Covid-19. In Jurnal Teknologi Dan Sistem Informasi Bisnis. https://doi.org/10.47233/jteksis.v3i2.248 Ramadhani, P. R., & Fauziah, P. Y. (2020). Hubungan Sebaya Dan Permainan Tradisional Pada Keterampilan Sosial Dan Emosional Anak Usia Dini. In Jurnal Obsesi Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.31004/obsesi.v4i2.502 Ramdani, N. S., Nugraha, H., & Hadiapurwa, A. (2021). Potensi Pemanfaatan Media Sosial Tiktok Sebagai Media Pembelajaran Dalam Pembelajaran Daring. In Akademika. https://doi.org/10.34005/akademika.v10i02.1406 Riwu, G. C. A., & Barus, G. (2023). Tingkat Kemampuan Orang Tua Dalam Meregulasi Penggunaan Smartphone Pada Anak Usia Dini. In Jurnal Obsesi Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.31004/obsesi.v7i2.4010 Rusdawati, R. (2019). Integrasi Teknologi Informasi Dalam Pembelajaran Anak Usia Dini. In Pedagogi Jurnal Ilmu Pendidikan. https://doi.org/10.24036/fip.100.v19i1.421.000-000 Setiawan, D., Hardiyani, I. K., Aulia, A., & Hidayat, A. (2022). Memaknai Kecerdasan Melalui Aktivitas Seni: Analisis Kualitatif Pengembangan Kreativitas Pada Anak Usia Dini. In Jurnal Obsesi Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.31004/obsesi.v6i5.2521 Sinaga, J., & Sinambela, J. (2023). Strategi Pembelajaran Efektif Melalui Permainan: Pengaruh Permainan Lego Dalam Meningkatkan Kreativitas Dan Kepandaian Pada Anak-Anak. https://doi.org/10.61404/jimad.v1i1.63 Sitorus, A. S. (2023). Hubungan Kepercayaan Diri dengan Keterampilan Sosial dan Emosional Anak. 11, 1–7. Solehudin, R. H. (2023). Pengenalan Digital Citizenship di Lingkungan Sekolah Dasar Introduction to Digital Citizenship in Elementary School Environment. 139–151. Solehudin, R. H., Budiarti, E., Hikmat, A., Gunawan, R., Yumirawati, E., Ahmad, N., Nahidl, A., & Anwar, S. (2023).The Effect of Family Economy on Education Opportunities ( Analysis of the Impact of Parents ’ Irregular Income on Millennial Children ’ s Educational Opportunities in the DKI Jakarta Area ). 5, 1095–1107. Sundqvist, P. (2019). Technological Knowledge in Early Childhood Education: Provision by Staff of Learning Opportunities. In International Journal of Technology and Design Education. https://doi.org/10.1007/s10798-019-09500-0 Supratman, S. H., Khuza’i, R., & Suhendi, H. (2022). Efektivitas Dakwah Melalui Media Sosial Tiktok Dalam Meningkatkan Nilai-Nilai Keberagamaan. In Jurnal Riset Komunikasi Penyiaran Islam. https://doi.org/10.29313/jrkpi.v2i1.748 Suryana, D., & Hijriani, A. (2021). Pengembangan Media Video Pembelajaran Tematik Anak Usia Dini 5-6 Tahun Berbasis Kearifan Lokal. In Jurnal Obsesi Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.31004/obsesi.v6i2.1413 Thaharah, A., & Mayar, F. (2022). Dampak Game Online Terhadap Perkembangan Sosial Emosional Anak Usia Dini 5-6 Tahun Di Taman Kanak-Kanak Al-Mukhlisin Pasaman Barat. In Jce (Journal of Childhood Education). https://doi.org/10.30736/jce.v6i2.1110 Timotheou, S., Miliou, O., Dimitriadis, Y., Sobrino, S. V., Giannoutsou, N., Cachia, R., Monés, A. M., & Ioannou, A. (2022). Impacts of digital technologies on education and factors influencing schools’ digital capacity and transformation: A literature review. In Education and Information Technologies (Vol. 28, Issue 6). Springer US. https://doi.org/10.1007/s10639-022-11431-8 Wolfe, S., Rojek, J., McLean, K., & Alpert, G. (2020). Social Interaction Training to Reduce Police Use of Force. Annals of the American Academy of Political and Social Science, 687(1), 124–145. https://doi.org/10.1177/0002716219887366 Zaini, H., & Dewi, K. (2017). Pentingnya Media Pembelajaran Untuk Anak Usia Dini. In Raudhatul Athfal Jurnal Pendidikan Islam Anak Usia Dini. https://doi.org/10.19109/ra.v1i1.1489